Relationship between BDNF expression in major striatal afferents, striatum morphology and motor behavior in the R6/2 mouse model of Huntington's disease. (21st November 2012) - Samadi, P.; Boutet, A.; Rymar, V. V.; Rawal, K.; Maheux, J.; Kvann, J.‐C.; Tomaszewski, M.; Beaubien, F.; Cloutier, J. F.; Levesque, D.; Sadikot, A. F.
<x xml:space="preserve">Abstract</x> Patients with Huntington's disease (HD) and transgenic mouse models of HD show neuronal loss in the striatum as a major feature, which contributes to cognitive and motor manifestations. Reduced expression of the neurotrophin brain‐derived neurotrophic factor (BDNF) in striatal afferents may play a role in neuronal loss. How progressive loss of BDNF expression in different cortical or subcortical afferents contributes to striatal atrophy and behavioral dysfunction in HD is not known, and may best be determined in animal models. We compared age‐dependent alterations of BDNF mRNA expression in major striatal afferents from the cerebral cortex, thalamus and midbrain in the R6/2 transgenic mouse model of HD. Corresponding changes in striatal morphology were quantified using unbiased stereology. Changes in motor behavior were measured using an open field, grip strength monitor, limb clasping and a rotarod apparatus. BDNF expression in cortical limbic and midbrain striatal afferents is reduced by age 4 weeks, prior to onset of motor abnormalities. BDNF expression in motor cortex and thalamic afferents is reduced by 6 weeks, coinciding with early motor dysfunction and reduced striatum volume. BDNF loss in afferents progresses until death at 13–15 weeks, correlating with progressive striatal neuronal loss and motor abnormalities. Mutant huntingtin protein expression in R6/2 mice results in progressive loss of BDNF in both cortical and subcortical striatal afferents. BDNF loss in limbic and dopaminergic striatal inputs may contribute to cognitive/psychiatric dysfunction in HD. Subsequent BDNF loss in cortical motor and thalamic afferents may accelerate striatal degeneration, resulting in progressive involuntary movements.